High-toughness cubic boron nitride composite material as well as preparation method and application thereof
By introducing silicon nitride into cubic boron nitride material and using its crystal structure phase change mechanism, the problems of short service life and poor impact resistance caused by the brittleness of cubic boron nitride material are solved, and high hardness and high toughness are achieved The combination of .
Patent Information
- Application Number
- CN202411501272.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In the prior art, cubic boron nitride materials have short service life and poor impact resistance due to their brittleness, making it difficult to improve the toughness of the material while maintaining high hardness.
By introducing silicon nitride as a binder, the crystal structure transformation mechanism of its α-phase and β-phase is used to consume energy when the material is stressed, enhancing the fracture toughness of the material.
While maintaining the high hardness of cubic boron nitride, it significantly improves the toughness and impact resistance of the material, extends the service life of the material, and optimizes its comprehensive performance.
Smart Images

Figure CN119462165A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of superhard material preparation, and in particular to a high-toughness cubic boron nitride composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern technology, superhard materials are increasingly used in industry, especially in the processing of hard materials, showing incomparable superiority. Superhard materials mainly include diamond and cubic boron nitride (cBN). Although diamond has the highest hardness, it is prone to carburization reaction under high temperature conditions, especially when processing materials containing iron elements, its strength drops rapidly, which greatly limits the application range of diamond. In contrast, cubic boron nitride has become one of the ideal processing materials in industries such as automobiles, aerospace, mechanical electronics and microelectronics because its hardness is second only to diamond, and it has excellent thermal stability, wide band gap, high thermal conductivity and chemical inertness to iron group metals and their alloys. Therefore, cubic boron nitride is considered to be a potential candidate material to replace diamond.
[0003] However, despite the extremely high hardness of cubic boron nitride, its inherent brittleness limits its service life in high-impact environments, seriously affecting its cutting efficiency and overall service life. In order to improve this problem, a variety of toughening solutions have been proposed in the prior art. However, hardness and toughness are often mutually exclusive. An increase in hardness is usually accompanied by a decrease in toughness. How to improve the toughness of the material while ensuring high hardness is still a huge technical challenge.
[0004] At present, common toughening technologies include introducing metal binders (such as Ni, Co, Al, etc.) into polycrystalline cubic boron nitride materials and improving toughness through high temperature and high pressure sintering. Although this type of method can enhance toughness to a certain extent, it often leads to a decrease in hardness, and the commonly used metal binders are not strong enough at high temperatures and cannot cope with harsh industrial environments. For this reason, some researchers have tried to use non-metallic toughening materials such as titanium nitride, aluminum nitride and zirconium dioxide to improve toughness. Although certain results have been achieved, the high sintering temperature and equipment requirements required have greatly increased the cost and process complexity.
[0005] In addition, using hard ceramics such as diamond instead of metal binders can further improve the hardness, but the toughness improvement effect is still not ideal. In recent years, nano- and submicron-sized polycrystalline cubic boron nitride has provided a new direction for toughening, but its ultra-high synthesis conditions and small sample size limit its practical industrial application.
[0006] In this context, silicon nitride (Si3N4) has become a promising binder material because of its high hardness and good toughness. The unique characteristic of silicon nitride is that it can undergo a phase transition from the α phase to the β phase under stress, consuming excess fracture energy and thus improving fracture toughness. For example, Chen Kexin and others achieved the transformation of α-Si3N4 to β-Si3N4 by precisely controlling the sintering parameters, and prepared a dual-phase ceramic material with different proportions of α / β phase interfaces, which greatly improved the toughness of the material.
[0007] Therefore, using silicon nitride as a binder to consume the fracture energy of cubic boron nitride through its phase change is expected to significantly improve the toughness of the material while maintaining the high hardness of cubic boron nitride. By adjusting the proportion of silicon nitride and its phase change conditions, the comprehensive performance of the material can be further optimized, providing an important technical path for the industrial production of cubic boron nitride; in order to improve the toughness while maintaining the hardness of cubic boron nitride, designing a new binder and preparation process is of great significance to promoting the industrial production of cubic boron nitride, improving the performance of this type of material, and promoting its application. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a high-toughness cubic boron nitride composite material, so as to solve the problem of short service life and poor impact resistance of the boron nitride composite material prepared by the conventional preparation method in the prior art due to brittleness, and to provide a method for improving the toughness of cubic boron nitride through the crystal structure phase change of silicon nitride binder.
[0009] The present invention provides a method for preparing a high-toughness cubic boron nitride composite material, comprising the following steps:
[0010] S1: using cubic boron nitride powder as a raw material, pretreating the raw material, and then mixing it with silicon nitride powder, wherein the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1-10%;
[0011] S2: the raw materials mixed in step S1 are loaded into a synthesis cavity of a domestic six-sided top press, and subjected to high temperature and high pressure synthesis treatment, followed by heat preservation and pressure preservation treatment; the conditions of the high temperature and high pressure synthesis treatment are: synthesis pressure 5 GPa, synthesis temperature 1000-1800°C;
[0012] S3: Cooling and depressurizing the product after the heat preservation in step S2 to obtain a composite material of cubic boron nitride and silicon nitride.
[0013] Compared with the prior art, the present invention discloses a method for preparing a high-toughness cubic boron nitride composite material, which has the following advantages: the present invention replaces the traditional metal binder (such as Ni, Co, etc.) in the prior art with a silicon nitride binder. Compared with the metal binder, silicon nitride consumes energy when the material is subjected to stress through its unique α-phase and β-phase crystal structure transformation, thereby enhancing the fracture toughness of the material, and absorbing the impact force in the microstructure of the material through the crystal phase transformation of silicon nitride, thereby improving the impact resistance of the material; and the introduction of silicon nitride not only does not significantly reduce the hardness of cubic boron nitride, but on the contrary effectively improves the toughness of the material through its unique structural phase transformation mechanism. This improvement ensures that the material can withstand high impact. Under impact load, the material will not be prone to brittle fracture like traditional cubic boron nitride, which significantly improves its service life and processing performance. Therefore, the material achieves excellent fracture toughness while maintaining ultra-high hardness; and in the above preparation method, the parameters of silicon nitride content, synthesis pressure, temperature and insulation and pressure holding time are closely related, and there is a synergistic effect between each other. By controlling the silicon nitride content (1-10%), synthesis temperature (1000-1800℃), synthesis pressure (5GPa), and precise setting of insulation and pressure holding time, the ideal phase change of the crystal structure of the composite material is ensured, thereby obtaining the perfect combination of high hardness and high toughness.
[0014] There is a contradiction between high hardness and high toughness in traditional cubic boron nitride materials. The preparation method of the high-toughness cubic boron nitride composite material in the present invention uses silicon nitride as a binder and utilizes the α-phase and β-phase structural transformation mechanism of silicon nitride. Under the premise of not reducing the hardness of cubic boron nitride, it successfully increases its toughness and significantly improves the overall performance of the composite material. This improvement not only overcomes the problem of material performance degradation at high temperatures caused by metal binders in traditional technologies, but also greatly extends the service life of the material, especially in industrial fine cutting and finishing; through the optimization design of material ratios, synthesis conditions and crystal structure phase change processes, the technical problem of "it is difficult to balance high hardness and high toughness of materials" in the background technology is successfully solved, and the fracture toughness and service life of cubic boron nitride materials are significantly improved. The core innovation of this technology lies in the introduction of binder silicon nitride and the control of its phase change process, which breaks through the limitations of existing superhard materials between high hardness and high toughness and promotes the widespread promotion of materials in industrial applications.
[0015] In a possible implementation, in the step S1, the particle size of the cubic boron nitride powder is 450-550 nm.
[0016] Compared with the prior art, the above technical solution can significantly improve the mechanical properties of the composite material by controlling the particle size of the cubic boron nitride powder at the nanometer level of 500nm. The cubic boron nitride powder with a smaller particle size can provide a higher specific surface area and a more uniform distribution, thereby forming a tighter bonding structure inside the material and reducing the generation of microscopic defects. Compared with materials with larger particle sizes, nano-scale powders can fully react with silicon nitride under high temperature and high pressure synthesis conditions to ensure that the crystal structure phase change in the composite material is more complete, especially the transformation from α-Si3N4 to β-Si3N4 is more complete, thereby enhancing the fracture toughness of the material. Through the precise control of the particle size of cubic boron nitride, it is ensured that the material has a higher reactivity and a more uniform structure during the synthesis process, thereby achieving an optimized balance between toughness and hardness and improving the comprehensive performance of the material.
[0017] In a possible implementation, in step S1, the pretreatment is performed by heat treating the cubic boron nitride powder at 300° C. for 2 hours before mixing the raw materials.
[0018] Compared with the prior art, the cubic boron nitride and silicon nitride composite material prepared by the above technical solution through heat treatment at 300°C for 2 hours performs better in hardness and toughness, and the overall structure of the material is denser and more stable. The pretreated powder can better participate in the subsequent high-temperature and high-pressure synthesis reaction, avoiding possible material failure or performance inconsistency. Therefore, the material is suitable for use in harsh environments, such as industrial cutting, wear-resistant materials and other high-demand scenarios; the surface impurities and activated powder particles are removed through pretreatment, so that the reaction in the subsequent synthesis process is more complete, and ultimately the material performance is significantly improved.
[0019] In a possible implementation, in step S1, the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 3-7%.
[0020] Compared with the prior art, by adopting the above technical solution, when the addition amount of silicon nitride is controlled at 3%-10%, it is evenly distributed with cubic boron nitride under high temperature and high pressure conditions to form a stable composite material structure. Within this range, the phase change process of silicon nitride is more stable, ensuring its toughening effect, and the proportion of 3%-10% also avoids the situation where the hardness decreases due to excessive silicon nitride. Silicon nitride not only acts as a binder to fill the material, but also effectively absorbs the fracture energy of the material under stress through its α-phase to β-phase crystal structure phase change. Therefore, an appropriate proportion of silicon nitride powder can significantly improve the fracture toughness of the material. By controlling the addition amount of silicon nitride, the full play of the silicon nitride phase change toughening mechanism is ensured, while maintaining the high hardness of the material, and optimizing and improving the comprehensive performance of the material.
[0021] In a possible implementation, in step S2, the conditions of the high temperature and high pressure synthesis treatment are: synthesis temperature 1300-1500° C., synthesis pressure 5 GPa.
[0022] Compared with the existing technology, the above technical solution can promote the phase change of silicon nitride from α phase to β phase through optimized temperature range and high pressure conditions, maximize the comprehensive performance of the composite material, and within the temperature range of 1300-1500℃, the crystal structure transformation process of silicon nitride can be carried out more stably, avoiding uneven material performance or defects caused by too high or too low temperature. At the same time, the high pressure of 5GPa can ensure the close bonding between the material particles, further improving the density and strength of the material; through this combination of temperature and pressure, cubic boron nitride and silicon nitride powder can fully react, so that the phase change of silicon nitride can effectively consume the fracture energy of the material and enhance toughness. The synthesis conditions can ensure that the material does not generate excessive internal stress during the formation process, thereby avoiding the problem of brittle fracture of the material.
[0023] In a possible implementation, in step S2, the heat preservation time is 15 minutes, and the pressure preservation time is 16 minutes.
[0024] Compared with the prior art, the above technical solution can precisely control the time of heat preservation and pressure holding in the key step of material synthesis, so that the microstructure of the material can undergo stable changes. Under high temperature and high pressure, the reaction between cubic boron nitride and silicon nitride requires a certain amount of time to complete, especially the phase change process from the α phase to the β phase of silicon nitride. The 15-minute heat preservation time can ensure that the phase change of silicon nitride is fully carried out, thereby improving the fracture toughness of the material. The 16-minute pressure holding time ensures the close bonding of the material particles under high pressure, reduces internal voids, and increases the overall density of the material.
[0025] In a possible implementation, in step S3, the cooling and depressurizing condition is: the product after the heat preservation treatment is naturally cooled to room temperature and then depressurized.
[0026] Compared with the existing technology, the above-mentioned technical scheme is adopted to achieve a balance between hardness and toughness of the prepared cubic boron nitride and silicon nitride composite material by naturally cooling to room temperature and then unloading the pressure. Moreover, since the internal stress is greatly reduced, the material exhibits better structural stability and durability during use. This cooling method makes the material suitable for application scenarios with high requirements for impact resistance, fatigue resistance and long-term stability, such as high-strength cutting tools or industrial fine processing. The speed of the cooling process is controlled to ensure that the temperature inside and outside the material is consistent, thereby avoiding cracks or structural defects caused by stress concentration, and finally achieving a balance between high hardness and high toughness, extending the service life of the material.
[0027] Another technical problem to be solved by the present invention is to provide a high-toughness cubic boron nitride composite material to solve the problems of short service life and poor impact resistance of conventional boron nitride composite materials due to brittleness.
[0028] In order to solve the above technical problems, the present invention provides a high-toughness cubic boron nitride composite material, wherein the cubic boron nitride and silicon nitride composite material is prepared by the above preparation method.
[0029] Compared with the prior art, the high-toughness cubic boron nitride composite material of the present application has the following advantages: the high-toughness cubic boron nitride composite material of the present invention replaces the metal binder (such as Ni, Co, etc.) in the prior art with silicon nitride as the binder, and during the crystal structure phase transition from the α phase to the β phase of silicon nitride, the energy of the material at the time of fracture can be absorbed and consumed, thereby increasing the toughness of the material; at the same time, silicon nitride is a ceramic material with relatively high hardness, and its introduction not only does not significantly reduce the hardness of the composite material, but on the contrary, through close combination with cubic boron nitride, the impact resistance and wear resistance of the material are enhanced, and finally the high-toughness cubic boron nitride composite material further obtains the final technical effect, that is, on the basis of maintaining high hardness, the high toughness and impact resistance of the material are achieved.
[0030] Another technical problem to be solved by the present invention is to provide an application of the cubic boron nitride composite material, wherein the application includes application of the cubic boron nitride composite material in industrial fine cutting and finishing.
[0031] Compared with the prior art, the application of a cubic boron nitride composite material in the present application has the following advantages: the traditional metal or ceramic cutting tool material in the prior art is changed to a composite material of cubic boron nitride and silicon nitride. The composite material has both extremely high hardness and enhanced fracture toughness. Cubic boron nitride provides excellent wear resistance and hardness, and the introduction of silicon nitride can absorb and consume local stress during the cutting process through the phase transition from α phase to β phase, avoiding the tool from breaking or failing under high stress or high temperature conditions. Due to the improved thermal stability of the material, the composite material can maintain its mechanical properties at higher temperatures, reducing the wear and deformation of the tool during processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is an X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Example 1-5;
[0033] Figure 2 is an X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Examples 6-10;
[0034] Figure 3is an X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Examples 11-15;
[0035] Figure 4 is the X-ray diffraction pattern of the cubic boron nitride prepared in Comparative Examples 1-5;
[0036] Figure 5 is a curve diagram showing the relationship between toughness and temperature of the cubic boron nitride and silicon nitride composite material prepared at a pressure of 5 GPa and a temperature of 1000° C. to 1800° C. in Examples 6-10;
[0037] Figure 6 This is a curve showing the relationship between hardness and temperature of the cubic boron nitride and silicon nitride composite material prepared at a pressure of 5 GPa and a temperature of 1000° C.-1800° C. in Examples 6-10. DETAILED DESCRIPTION
[0038] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.
[0039] The present invention provides a method for preparing a high-toughness cubic boron nitride composite material, comprising the following steps:
[0040] S1: using cubic boron nitride powder as a raw material, pretreating the raw material, and then mixing it with silicon nitride powder, wherein the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1-10%;
[0041] S2: the raw materials mixed in step S1 are loaded into a synthesis cavity of a domestic six-sided top press, and subjected to high temperature and high pressure synthesis treatment, followed by heat preservation and pressure preservation treatment; the conditions of the high temperature and high pressure synthesis treatment are: synthesis pressure 5 GPa, synthesis temperature 1000-1800°C;
[0042] S3: Cooling and depressurizing the product after the heat preservation in step S2 to obtain a composite material of cubic boron nitride and silicon nitride.
[0043] As a preferred solution, in step S1, the particle size of the cubic boron nitride powder is 450-550 nm.
[0044] As a preferred solution, in step S1, the pretreatment method is: before the raw materials are mixed, the cubic boron nitride powder is heat treated at 300° C. for 2 hours.
[0045] As a preferred solution, in step S1, the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 3-7%.
[0046] As a preferred solution, in step S2, the conditions of the high temperature and high pressure synthesis treatment are: synthesis temperature 1300-1500°C, synthesis pressure 5GPa.
[0047] As a preferred solution, in step S2, the heat preservation time is 15 minutes, and the pressure preservation time is 16 minutes.
[0048] As a preferred solution, in step S3, the cooling and pressure relief condition is: the product after the heat preservation treatment is naturally cooled to room temperature and then the pressure is relieved.
[0049] The present invention also provides a high-toughness cubic boron nitride composite material, wherein the cubic boron nitride and silicon nitride composite material is prepared by the above-mentioned preparation method.
[0050] The present invention also provides an application of the cubic boron nitride composite material, and the application includes application of the cubic boron nitride composite material in industrial fine cutting and finishing.
[0051] The above scheme of the present invention is further described below in combination with specific data and experimental methods:
[0052] Example 1
[0053] Example 1 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0054] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1%;
[0055] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1000°C, and then stop heating;
[0056] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 1 .
[0057] Example 2
[0058] Example 2 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0059] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1%;
[0060] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1200°C, and then stop heating;
[0061] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 1 .
[0062] Example 3
[0063] Example 3 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0064] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1%;
[0065] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1400°C, and then stop heating;
[0066] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 1 .
[0067] Example 4
[0068] Example 4 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0069] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1%;
[0070] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1600°C, and then stop heating;
[0071] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 1 .
[0072] Example 5
[0073] Example 5 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0074] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1%;
[0075] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1800°C, and then stop heating;
[0076] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 1 .
[0077] Example 6
[0078] Example 6 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0079] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 5%;
[0080] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1000°C, and then stop heating;
[0081] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 2 .
[0082] Example 7
[0083] Example 7 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0084] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 5%;
[0085] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1200°C, and then stop heating;
[0086] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 2 .
[0087] Example 8
[0088] Example 8 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0089] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 5%;
[0090] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1400°C, and then stop heating;
[0091] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 2 .
[0092] Example 9
[0093] Example 9 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0094] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 5%;
[0095] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1600°C, and then stop heating;
[0096] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 2 .
[0097] Example 10
[0098] Embodiment 10 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0099] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 5%;
[0100] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1800°C, and then stop heating;
[0101] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 2 .
[0102] Embodiment 11
[0103] Example 11 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0104] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 10%;
[0105] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1000°C, and then stop heating;
[0106] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 3 .
[0107] Example 12
[0108] Example 12 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0109] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 10%;
[0110] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1200°C, and then stop heating;
[0111] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 3 .
[0112] Embodiment 13
[0113] Example 13 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0114] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 10%;
[0115] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1400°C, and then stop heating;
[0116] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 3 .
[0117] Embodiment 14
[0118] Example 14 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0119] S1: preheating cubic boron nitride powder at 300°C for 2h, adding silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 10%;
[0120] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1600°C, and then stop heating;
[0121] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 3 .
[0122] Embodiment 15
[0123] Example 15 provides a high-toughness cubic boron nitride composite material and a preparation method thereof. The high-toughness cubic boron nitride composite material is prepared by the following method:
[0124] S1: preheating cubic boron nitride powder at 300°C for 2h, adding % silicon nitride powder and mixing evenly, and processing into a cylinder with a diameter of 4mm and a height of 2mm; the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 10%;
[0125] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1800°C, and then stop heating;
[0126] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 3 .
[0127] Comparative Example 1
[0128] Comparative Example 1 provides a boron nitride composite material and a preparation method thereof, the difference being that in step S1, the amount of silicon nitride powder added is 0wt.%, that is, no silicon nitride powder is added, and the boron nitride composite material is prepared by the following method:
[0129] S1: Preheat the cubic boron nitride powder at 300°C for 2 h and process it into a cylinder with a diameter of 4 mm and a height of 2 mm;
[0130] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1000°C, and then stop heating;
[0131] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 4 .
[0132] Comparative Example 2
[0133] Comparative Example 2 provides a boron nitride composite material and a preparation method thereof, the difference being that in step S1, the amount of silicon nitride powder added is 0wt.%, that is, no silicon nitride powder is added, and the boron nitride composite material is prepared by the following method:
[0134] S1: Preheat the cubic boron nitride powder at 300°C for 2 h and process it into a cylinder with a diameter of 4 mm and a height of 2 mm;
[0135] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1200°C, and then stop heating;
[0136] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 4 .
[0137] Comparative Example 3
[0138] Comparative Example 3 provides a boron nitride composite material and a preparation method thereof, the difference being that in step S1, the amount of silicon nitride powder added is 0wt.%, that is, no silicon nitride powder is added, and the boron nitride composite material is prepared by the following method:
[0139] S1: Preheat the cubic boron nitride powder at 300°C for 2 h and process it into a cylinder with a diameter of 4 mm and a height of 2 mm;
[0140] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1400°C, and then stop heating;
[0141] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 4 .
[0142] Comparative Example 4
[0143] Comparative Example 4 provides a boron nitride composite material and a preparation method thereof, the difference being that in step S1, the amount of silicon nitride powder added is 0wt.%, that is, no silicon nitride powder is added, and the boron nitride composite material is prepared by the following method:
[0144] S1: Preheat the cubic boron nitride powder at 300°C for 2 h and process it into a cylinder with a diameter of 4 mm and a height of 2 mm;
[0145] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1600°C, and then stop heating;
[0146] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 4 .
[0147] Comparative Example 5
[0148] Comparative Example 5 provides a boron nitride composite material and a preparation method thereof, the difference being that in step S1, the amount of silicon nitride powder added is 0wt.%, that is, no silicon nitride powder is added, and the boron nitride composite material is prepared by the following method:
[0149] S1: Preheat the cubic boron nitride powder at 300°C for 2 h and process it into a cylinder with a diameter of 4 mm and a height of 2 mm;
[0150] S2: Put the raw materials processed in step S1 into a high-temperature and high-pressure synthesis block. Keep the temperature for 15 minutes and the pressure for 16 minutes under the conditions of synthesis pressure of 5 GPa and synthesis temperature of 1800°C, and then stop heating;
[0151] S3: The sample is naturally cooled to room temperature and then the pressure is released. The X-ray diffraction results of the composite materials of cubic boron nitride and silicon nitride prepared under different temperature conditions are shown in Figure 4 .
[0152] The experiments involved in the above embodiments were completed by experimental assembly of a domestic six-sided top press.
[0153] Figure 1 is an X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Example 1, Example 2, Example 3, Example 4, and Example 5; Figure 2 is the X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Example 6, Example 7, Example 8, Example 9, and Example 10; Figure 2 It can be seen from the XRD diagram that under the conditions of Example 8 of the present invention, that is, when the temperature is 1400°C, the silicon nitride α phase begins to transform into the β phase, and the sample is now a composite phase of silicon nitride dual phase and cubic boron nitride. Figure 3 is an X-ray diffraction pattern of the cubic boron nitride and silicon nitride composite material prepared in Example 11, Example 12, Example 13, Example 14, and Example 15; Figure 4 is the X-ray diffraction pattern of the cubic boron nitride prepared in Comparative Examples 1-5; Figure 4It can be seen from the XRD graph that under the conditions of comparative example 5 of the present invention, that is, at a temperature of 1800°C, cubic boron nitride is substantially completely converted into hexagonal boron nitride. At the same time, due to the simple high temperature and high pressure sintering of cBN in the preparation methods of comparative examples 1-5, the samples are very brittle and have very low toughness, while the toughness of the embodiments of the present invention can be improved by adding a sintering aid.
[0154] Through the test results in the preparation methods of Examples 1-15, the effects of different added masses of silicon nitride (1wt.%, 5wt.%, 10wt.%) in the composite material with cubic boron nitride are as follows:
[0155] 1% silicon nitride: At this addition, the amount of silicon nitride is small and the toughening effect is not significant, mainly because the content of silicon nitride is not enough to form a uniformly distributed bonding phase or sufficient α phase to β phase transformation inside the material, resulting in limited improvement in the fracture toughness of the material;
[0156] 5% silicon nitride: Experiments show that at this content, the fracture toughness and hardness of the composite material show the best balance. 5wt.% silicon nitride is enough to produce a phase transition from α phase to β phase. This phase transition process can absorb the energy during fracture and effectively improve toughness. In addition, 5wt.% silicon nitride content will not significantly reduce the hardness of the material, satisfying the balance between high hardness and toughness, and is the addition ratio with the best technical effect.
[0157] 10% Silicon Nitride: At 10wt.%, the toughening effect of silicon nitride is further improved, but it will also affect the overall hardness of the material. Too much silicon nitride may cause a slight decrease in the high hardness of the composite material, which is not as ideal as the balance of hardness and toughness at 5wt.%.
[0158] Figure 5 is a curve showing the relationship between fracture toughness and temperature of the cubic boron nitride and silicon nitride composite material prepared at a pressure of 5 GPa and a temperature of 1000° C. to 1800° C. in Examples 6, 7, 8, 9 and 10;
[0159] Figure 6 is a curve showing the relationship between hardness and temperature of the cubic boron nitride and silicon nitride composite material prepared at a pressure of 5 GPa and a temperature of 1000° C. to 1800° C. in Examples 6, 7, 8, 9 and 10;
[0160] Figure 5 , Figure 6 It also shows that the composite material of cubic boron nitride and silicon nitride prepared by the present invention at a pressure of 5 GPa and a temperature of 1400°C can improve the fracture toughness to 9.58 MPa·m while retaining high hardness. 1 / 2, excellent mechanical properties and mechanical properties, with better comprehensive performance, providing a binder crystal structure phase change to increase the toughness of polycrystalline cubic boron nitride and its preparation method.
[0161] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
[0162] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a high-toughness cubic boron nitride composite material, characterized in that: The following steps are involved: S1: using cubic boron nitride powder as a raw material, pretreating the raw material, and then mixing it with silicon nitride powder, wherein the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 1-10%; S2: the raw materials mixed in step S1 are loaded into a synthesis cavity of a domestic six-sided top press, and subjected to high temperature and high pressure synthesis treatment, followed by heat preservation and pressure preservation treatment; the conditions of the high temperature and high pressure synthesis treatment are: synthesis pressure 5 GPa, synthesis temperature 1000-1800°C; S3: Cooling and depressurizing the product after heat preservation in step S2 to obtain a composite material of cubic boron nitride and silicon nitride.
2. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In the step S1, the particle size of the cubic boron nitride powder is 450-550 nm.
3. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In the step S1, the pretreatment method is: before the raw materials are mixed, the cubic boron nitride powder is heat treated at 300° C. for 2 hours.
4. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In the step S1, the molar ratio of the silicon nitride powder to the cubic boron nitride powder is 3-7%.
5. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In step S2, the conditions of the high temperature and high pressure synthesis treatment are: synthesis temperature 1300-1500° C., synthesis pressure 5 GPa.
6. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In step S2, the heat preservation time is 15 minutes, and the pressure preservation time is 16 minutes.
7. The method for preparing the high-toughness cubic boron nitride composite material according to claim 1, characterized in that: In step S3, the cooling and depressurizing conditions are: the product after the heat preservation treatment is naturally cooled to room temperature and then depressurized.
8. A high-toughness cubic boron nitride composite material, characterized in that: The cubic boron nitride and silicon nitride composite material is prepared by any preparation method according to claims 1-7.
9. An application of the cubic boron nitride composite material according to claim 8, characterized in that: The application includes application of the cubic boron nitride composite material in industrial fine cutting and finishing.
Citation Information
Patent Citations
Cubic boron nitride blade and preparation method thereof
CN102049538A
Superhard composite abrasive material and preparation method thereof
CN104293291A
Production of cubic boron nitride calcined compact
JP1989131067A
Cubic boron nitride composite sintered body, production method thereof and cutting tool, abrasion-resistant tool and grinding tool
JP2015202981A
Shock consolidation of cubic boron nitride with whiskers of silicon compounds
US4863881A